Sanctions in Financial Services: Developing a Conducive Culture in Financial Industry in Indonesia - Johan, Suwinto (Bina Nusantara University, 2022)
The research proposed adjustments to sanctions for criminal acts in the financial services industry in accordance with Law No. 21/2011. Based on the Law of the Republic of Indonesia No. 21/2011, the Indonesian Financial Services Authority (FSA) had the authority to regulate the financial industry in Indonesia. FSA had enormous capacity, including the authority to impose criminal sanctions in the financial services industry. However, criminals in the financial sector still recurred after establishing the OJK. One of financial services industry crimes began with Bank Indonesia Liquidity Assistance due to the 1998 Asian crisis, and the crisis due to the COVID-19 pandemic had resulted in several criminal acts in the financial industry such as the Bank Bukopin case and several cases of insurance companies such as Jiwasraya insurance. The research applied a normative juridical method. It concludes that criminal sanctions in the financial services industry can be imposed on individuals and/or corporations. This criminal sanction is imposed if someone deliberately ignores, does not fulfill, or hinders the exercise of the FSA's authority or deliberately ignores and/or does not carry out the FSA's written orders. A person's definition needs to be clarified in his/her position at a financial service institution to be subject to a criminal offense.